Survival after Lung Volume Reduction in Chronic Obstructive Pulmonary Disease: Insights from Small Airway Pathology - Hogg, James C. (American Thoracic Society, 2007)
Rationale: COPD is associated with reduced life expectancy. Objectives: To determine the association between small airway pathology and long-term survival after lung volume reduction in chronic obstructive pulmonary disease (COPD) and the effect of corticosteroids on this pathology. Methods: Patients with severe (GOLD-3) and very severe (GOLD-4) COPD (n = 101) were studied after lung volume reduction surgery. Respiratory symptoms, quality of life, pulmonary function, exercise tolerance, chest radiology, and corticosteroid treatment status were assessed preoperatively. The severity of luminal occlusion, wall thickening, and the presence of small airways containing lymphoid follicles were determined in resected lung tissue. Kaplan-Meier survival analysis and Cox proportional hazards models were used to determine the relationship between survival and small airway pathology. The effect of corticosteroids on this pathology was assessed by comparing treated and untreated groups. Measurements and Main Results: The quartile of subjects with the greatest luminal occlusion, adjusted for covariates, died earlier than subjects who had the least occlusion (hazard ratio, 3.28; 95% confidence interval, 1.55–6.92; P = 0.002). There was a trend toward a reduction in the number of airways containing lymphoid follicles (P = 0.051) in those receiving corticosteroids, with a statistically significant difference between the control and oral ± inhaled corticosteroid–treated groups (P = 0.019). However, corticosteroid treatment had no effect on airway wall thickening or luminal occlusion. Conclusions: Occlusion of the small airways by inflammatory exudates containing mucus is associated with early death in patients with severe emphysema treated by lung volume reduction surgery. Corticosteroid treatment dampens the host immune response in these airways by reducing lymphoid follicles without changing wall thickening and luminal occlusion.